Tourism Impact on the Cultural Heritage of Countries in the Middle East - Ahmed, Nadia (Journal of Applied Geographical Studies, 2024)
Purpose: The main objective of this study was to explore the tourism impact on cultural heritage of countries in the Middle East. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the tourism impact on cultural heritage of countries in the Middle East. Preliminary empirical review revealed that tourism has both positive and negative effects on the region's cultural heritage. While it significantly contributes to the economy and fosters cultural exchange, it also poses challenges such as overcrowding and cultural commodification. The study emphasizes the importance of sustainable tourism practices and responsible heritage management. Cultural ecology, cultural conservation, and dependency theories provided valuable frameworks for understanding this complex relationship. The findings benefit policymakers, site managers, local communities, and the tourism industry by guiding the development of strategies that protect cultural heritage while harnessing tourism's economic potential, contributing to a more balanced approach to tourism development in the Middle East. Unique Contribution to Theory, Practice and Policy: The Cultural Ecology Theory, Cultural Conservation Theory and the Dependency Theory may be used to anchor future studies on cultural heritage. The study suggested a set of comprehensive recommendations. These recommendations emphasize the importance of heritage conservation and responsible tourism practices. They include the development of robust heritage management plans, enhanced visitor education, and community engagement. Encouraging tourism diversification, sustainable infrastructure development, and capacity building are also essential. Furthermore, the study highlights the significance of ongoing research, marketing strategies that promote cultural richness, and intergovernmental coordination. By implementing these measures, Middle Eastern countries can achieve a harmonious balance between cultural heritage preservation and the economic benefits of tourism, ensuring the long-term sustainability of both.